'YESTERYEAR' - Harris, C.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
During the course of a recent visit to Simonstown I parked my car on the heights of Jubilee Square from which vantage point I could gaze down upon the naval dockyard and the buildings which today form only a portion of the vast naval complex which spreads its tentacles from one end of Simonstown to the other, and even beyond.